2011
DOI: 10.1007/s11033-011-0695-4
|View full text |Cite
|
Sign up to set email alerts
|

MCP-1 −2518 A/G functional polymorphism is associated with increased susceptibility to active pulmonary tuberculosis in Tunisian patients

Abstract: Monocyte chemoattractant protein-1 (MCP-1) plays crucial role in protective immunity against Mycobacterium tuberculosis (MT). In this study, we examined whether single nucleotide polymorphism (SNP) -2518 A/G (rs 1024611) of MCP-1 affect the susceptibility to active tuberculosis (TB) in Tunisian populations. Genomic DNA from patients with active TB (168 cases of pulmonary TB and 55 cases of extrapulmonary TB) and ethnically controls (150 cases) was genotyped for the MCP-1 -2518 A/G SNP by polymerase chain react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…The results of the study are consistent with those of previous reports regarding the association between MCP-1 -2518A/G polymorphisms and tuberculosis in Mexicans, Koreans, Peruvians, Tunisians, and Zambians (Flores-Villanueva et al, 2005;Buijtels et al, 2008;Ganachari et al, 2010;Ben-Selma et al, 2011). Others have reported different results, such as in South African Coloreds, Indians, and Ghanaians (Alagarasu et al, 2009;Moller et al, 2009;Thye et al, 2009).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of the study are consistent with those of previous reports regarding the association between MCP-1 -2518A/G polymorphisms and tuberculosis in Mexicans, Koreans, Peruvians, Tunisians, and Zambians (Flores-Villanueva et al, 2005;Buijtels et al, 2008;Ganachari et al, 2010;Ben-Selma et al, 2011). Others have reported different results, such as in South African Coloreds, Indians, and Ghanaians (Alagarasu et al, 2009;Moller et al, 2009;Thye et al, 2009).…”
Section: Discussionsupporting
confidence: 91%
“…Thus, further studies are needed to assess the effect of additional interactions in different ethnicities and to validate our results. The molecular mechanism of the association between the MCP-1 gene and PTB may be that the MCP-1 is a potent chemotactic factor for monocytes (Flores-Villanueva et al, 2005;Ben-Selma et al, 2011), which plays critical roles in the recruitment of macrophages and T lymphocytes for controlling the dissemination of Mycobacterium TB (Xu et al, 2009). The -2518A/G polymorphism in the MCP-1 regulatory region influences the levels of MCP-1 expression in response to inflammatory stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…However, the concentration of G-CSF needs to be optimized to make sure that the dose of G-CSF does not induce PMN-induced acute lung injury and possibly, ARDS. It has also been demonstrated that MCP-1 polymorphism is associated with increased susceptibility to Mycobacterium tuberculosis infection (81, 82) and bacterial peritonitis (83). …”
Section: Discussionmentioning
confidence: 99%
“…The migration of these cells is orchestrated by chemokines and their receptors. In this context, one member of the C‐C chemokine family, namely monocyte chemoattractant protein‐1 (MCP‐1), also referred to as CCL2 (the chemokine (C‐C motif) ligand 2), is considered to be a potent chemotactic factor for monocytes (Ben‐Selma, Harizi, & Boukadida, ; Flores‐Villanueva et al., ). Human MCP‐1, which is composed of 76 amino acids and has a size of 13 kDa, plays an essential role in the innate immune response against microbial infection (Deshmane, Kremlev, Amini, & Sawaya, ; Serbina, Jia, Hohl, & Pamer, ; Van Coillie, Van Damme, & Opdenakker, ).…”
Section: Candidate Genes and The Risk Of Developing Tbmentioning
confidence: 99%